Association between elder abuse and poor sleep: A cross-sectional study among rural older Malaysians - Yunus, R.M.; Wazid, S.W.; Hairi, N.N.; Choo, W.Y.; Hairi, F.M.; Sooryanarayana, R.; Ahmad, S.N.; Razak, I.A.; Peramalah, D.; Aziz, S.A.; Mohamad, Z.L.; Mohamad, R.; et al. (Public Library of Science, 2017)
Objectives To examine the association between elder abuse and poor sleep using a Malay validated version of Pittsburgh Sleep Quality Index (PSQI). Design This study was divided into two phases. Phase I tested the construct validity and reliability of the Malay version of PSQI. Phase II was a population-based, cross-sectional study with a multi-stage cluster sampling method. Home-based interviews were conducted by trained personnel using a structured questionnaire, to determine exposure and outcome. Setting Kuala Pilah, a district in Negeri Sembilan which is one of the fourteen states in Malaysia. Participants 1648 community-dwelling older Malaysians. Results The Malay version of PSQI had significant test re-test reliability with intra-class correlation coefficients of 0.62. Confirmatory factor analyses revealed that one factor PSQI scale with three components (subjective sleep quality, sleep latency, and sleep disturbances) was most suitable. Cronbach’s Alpha was 0.60 and composite reliability was 0.63. PSQI scores were highest among neglect (4.11), followed by physical (4.10), psychological (3.96) and financial abuse (3.60). There was a dose-response relationship between clustering of abuse and PSQI scores; 3.41, 3.50 and 3.84 for “no abuse”, “1 type of abuse” and “2 types or more”. Generalized linear models revealed six variables as significant determinants of sleep quality–abuse, co-morbidities, self-rated health, income, social support and gait speed. Among abuse subtypes, only neglect was significantly associated with poor sleep. Conclusion The Malay PSQI was valid and reliable. Abuse was significantly associated with poor sleep. As sleep is essential for health and is a good predictor for mortality among older adults, management of abuse victims should entail sleep assessment. Interventions or treatment modalities which focus on improving sleep quality among abuse victims should be designed.